Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

(3y - 1)/4 + (2y + 3)/3 = (1 - 7y)/6​

Sagot :

3(3y-1)/12+4(2y+3)/12=(1-7y)/6
9y-3+8y+12/12=1-7y/6
17y+8/2=1-7y
17y+8=2-14y
3y=-6
y=-2

Answer:

y= -7/31 ????

Step-by-step explanation:

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.